Activistes féministes: Francophone Women Writers and International Human Rights. (November 2020) - Rice, Alison
Several prominent contemporary Francophone women writers have embraced activism in compelling forms. In her written creations, Maïssa Bey from Algeria has continually called attention to the lack of women's rights in her homeland; she has also initiated writing workshops for women to reflect and express themselves. Fatou Diome, who left Senegal for Strasbourg, has shed light in her work on racism and sexism that African immigrants often face in Europe, and she has created an association in her homeland to help individuals become financially solvent. Yanick Lahens from Haiti has similarly devoted herself to activist endeavours on her island, including co-founding a library and working with youth after the earthquake. As these authors seek to create compassion through writing, they also promote empathy through their engagement outside the text, empowering people of various backgrounds by providing them with literacy skills, business acumen, and a sense that their story matters.